Exploring Ethical Requirements Elicitation for Applications in the Context of AI - Cerqueira, José Antonio Siqueira de; Canedo, Edna Dias (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
Ethical concerns arises from the proliferation of Artificial Intelligence (AI) based systems in use. AI ethics has been approached mainly in guidelines and principles, not providing enough practical guidance for developers. Hence, we aim to present RE4AI Ethical Guide and its evaluation. We used the Design Science Research methodology to understand the problem, present the guide and evaluate it through a focus group. The Guide is composed of 26 cards across 11 principles. We evaluated it with 5 AI professionals and our preliminary results reveal that it has the potential to facilitate the elicitation of ethical requirements. Thus, we contribute to bridge the gap between principles and practice by assisting developers to elicit ethical requirements and operationalise ethics in AI.